2012
DOI: 10.3389/fpsyg.2012.00175
|View full text |Cite
|
Sign up to set email alerts
|

Remembering Another Aspect of Forgetting

Abstract: Although forgetting is most often thought of in terms of declines in performance (response loss or impairment), another class of memory phenomena, the forgetting of stimulus attributes, has begun to attract experimental attention. In non-human animals, the loss of memory for stimulus features is reflected in the flattening of stimulus generalization gradients as well as in the attenuation of the disrupting effect of a shift in context at testing. In both cases, a delay between the learning episode and testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 100 publications
3
50
0
Order By: Relevance
“…To date, theories of memory precision all share the idea that the passage of time is required in order for generalized responding to occur (Biedenkapp and Rudy, 2007;Jasnow et al, 2012;Lynch et al, 2013;Matynia et al, 2008;Wiltgen and Silva, 2007;Winocur et al, 2007). The current data suggest, in some cases, the loss of memory precision does not require a significant passage of time (ie, several or more days) and can be dependent upon the maintenance of the originally formed memory trace during memory consolidation.…”
Section: Gabab(1a) Receptors and Fear Generalizationmentioning
confidence: 58%
See 2 more Smart Citations
“…To date, theories of memory precision all share the idea that the passage of time is required in order for generalized responding to occur (Biedenkapp and Rudy, 2007;Jasnow et al, 2012;Lynch et al, 2013;Matynia et al, 2008;Wiltgen and Silva, 2007;Winocur et al, 2007). The current data suggest, in some cases, the loss of memory precision does not require a significant passage of time (ie, several or more days) and can be dependent upon the maintenance of the originally formed memory trace during memory consolidation.…”
Section: Gabab(1a) Receptors and Fear Generalizationmentioning
confidence: 58%
“…According to the transformation hypothesis of memory function over time, detailed context-specific memories are initially dependent on the hippocampus, but are transformed into schematic (less specific) memories as they are stored in the neocortex, resulting in generalized memory recall (Frankland et al, 2006;Frankland et al, 2001;Kim and Fanselow, 1992;McGaugh, 1966;Vetere et al, 2011;ZolaMorgan and Squire, 1990). The gradual decline in memory precision over time (Jasnow et al, 2012) may be due to some modulation of memory storage in the neocortex or its potential interaction with the ventral hippocampus (Cullen et al, 2015). Given the results presented here and previous findings within GABA B(1a) KO mice that have normal hippocampal GABA B(1a) autoreceptors (Gassmann and Bettler, 2012), we conclude that the effect of CGP, and thus the role of GABA B(1a) receptors in fear generalization, occurs through presynaptic mechanisms on glutamatergic terminals.…”
Section: Gabab(1a) Receptors and Fear Generalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 14 d after training, the groups tested in a neutral context had performance comparable to the group in the same (training) context (Zhou and Riccio 1996). This effect has been replicated by several labs (for review, see Jasnow et al 2012).In recent years, several hypotheses have been developed to explain the phenomenon of fear generalization in animal models. Hippocampal-dependent memory, such as memory for context, undergoes a transfer from short-term hippocampal stores to more long-term cortical stores, a process known as systems consolidation (Kim and Fanselow 1992;Anagnostaras et al 2001;Wiltgen et al 2006;Jasnow et al 2012).…”
mentioning
confidence: 77%
“…In recent years, several studies have demonstrated in rodents, as in humans, that fear memories are more prone to generalize over time as a result of stimulus discrimination failure (Biedenkapp and Rudy 2007;Wiltgen and Silva 2007). This in large part has been attributed to the forgetting of specific contextual-spatial features resulting in the broadening or generalization of fear across distinct contexts (Jasnow et al 2012). In contrast, demonstrations of fear incubation in the rodent Pavlovian fear conditioning preparation have been more sparse, with a large body of research failing to observe incubation across rodent strains and conditioning parameters (Frankland et al 2004;Gale et al 2004;Poulos et al 2009), yet a series of reports by colleagues (2009a,b, 2010) have reported fear incubation with significant modification of standard fear conditioning procedures.…”
mentioning
confidence: 99%